The Witness Stand and Lawrence S. Wrightsman, Jr. - Willis-Esqueda, Cynthia; Bornstein, Brian H. (Springer New York : Imprint: Springer, 2016)
This unique volume salutes the work of pioneering forensic psychologist Lawrence S. Wrightsman, Jr., by presenting current theorizing and research findings on issues that define the field of psychology and law. Ongoing topics in witness behaviors, suspect identification, and juror decision making illustrate how psychology and law complement and also conflict at various stages in legal processes. The book also sheds light on evolving areas such as DNA exonerations, professional trial consulting, and jury selection strategies, and the distinct challenges and opportunities these issues present. Noted contributors to the book include Wrightsman himself, who offers salient observations on the field that he continues to inspire.  Featured among the topics:  The credibility of witnesses. Psychological science on eyewitness identification and the U.S. Supreme Court. False confessions, from colonial Salem to today. Identifying juror bias: toward a new generation of jury selection research. Law and social science: how interdisciplinary is interdisciplinary enough? Race and its place in the American legal system. With its diverse mix of perspectives and methodologies, The Witness Stand and Lawrence S. Wrightsman, Jr. will interest forensic researchers in academic and applied settings, as well as individuals working in the legal system, such as attorneys, judges and law enforcement personnel.